Aktivitas Enzim Protease Beauveria bassiana Galur Lokal Sulawesi Selatan - Hilda Karim (Bionature, 2008)
Activity a protease enzyme hardly related to ability of mould elaborates protein component found on substrate that is casein. Temperature and hydrogen ion exponent is one of environmental factor influencing enzymatic activity. Initial step of determination of maximum hydrogen ion exponent by the way of giving treatment of initial hydrogen ion exponent so that obtainable and determined optimum pH B. bassiana subprovince Maros and sub-province Enrekang by seeing highest enzymatic activity indicator. Based on treatment of determination of optimum pH that is certain hydrogen ion exponent of which can cause highest activity to protease enzyme hence obtained by result that mould isolate B. bassiana sub-province Maros and also sub-province Enrekang both having enzymatic activity with optimum pH at hydrogen ion exponent 7 where enzymatic activity from each mould isolate successively that is 0,301 unit/mL/minutes and 0,682 unit/mL/minutes.